Я - вор в законе. Облава - Сухов Евгений Евгеньевич (Я - вор в законе, 2003)
Экземпляры: ф.16 (2004) / Инвентарный номер: 45125 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 91 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44